Enhancing Quality of Life Through Self-Esteem and Empowerment Therapy in Chronically Ill Elderly: Systematic Review - Dr. Nutan Kumri; Ms. Rachna; Ms. SnehaPriya; Ms. Purnima (The Bioscan, 2026)
Background: Chronic illnesses significantly compromise quality of life (QOL) among elderly populations. Psychological constructs such as self-esteem and empowerment are increasingly recognized as essential determinants of well-being and successful aging. Objective: To systematically evaluate the effectiveness of self-esteem and empowerment-based interventions in improving quality of life among elderly individuals with chronic illnesses.